Estudio del pH y la concentración de glicerol para la producción de antígeno recombinante de Plasmodium vivax usando Pichia pastoris - Pillaca-Pullo y Colls., Omar (2018)
The methylotrophic yeast Pichia pastoris is widely used as a eukaryotic system for expressing recombinant proteins. Over 500 recombinant proteins were expressed by P. pastoris with expression levels reaching up to 80% of total secreted proteins and up to 30% of total cell protein. The production process consists of a growth phase with glycerol and then an induction phase with methanol. Control culture conditions (pH, temperature, concentration of inducer, carbon and nitrogen source, etc.) are important for the growth of yeast to the production of the protein factors. On the other hand, malaria is a disease of great importance to global public health because of it is high prevalence mainly in tropical countries. In recent years there has been a breakthrough in the research of vaccines against Plasmodium species within the major antigenic proteins are the Antigen Membrane Apical (AMA) and Merozoite Protein Surface (MSP) that can be administered singly, in combination or conjugate (chimera). In this study were evaluated initial medium pH (3.0 to 8.0) and the initial concentration of glycerol (0 to 60 gL-1) on growth of yeast, after analyzed amounts of dry biomass obtained at each point, were taken three pH values (6.0, 7.0 and 8.0) and three different concentrations of glycerol (10, 30 and 50 gL-1) and experiments were performed with combinations of these parameters. The data showed that the best condition producing the recombinant antigen of Plasmodium vivax (PvAMA166-MSP119) was at pH 7.0 and 30 gL-1 of glycerol and that high concentrations of glycerol cause higher final pH decrease affecting the production of recombinant antigen and increasing the risk of proteolysis. Finally it is recommended to evaluate this production in bioreactor where adequate control of pH is carried with use of ammonium hydroxide to adjust the pH which is also used by the yeast as a nitrogen source.